Effects of key design parameters of tine furrow opener on soil seedbed properties - Xiangcai, Zhang; Hongwen, Li; Ruicheng, Du; Shaochun, Ma; Jin, He; Qingjie, Wang; Wangzhi, Chen; Zhiqi, Zheng; Zhiqiang, Zhang (International Journal of Agricultural and Biological Engineering, 2016)
The structural parameters of tine furrow openers have significant effects on soil property of seed furrow in no-till planting, thereby affecting crop growth and yields. In order to analyze the effects of key parameters of tine furrow openers on soil properties (soil bulk density, soil water-stable aggregates (WSA), and soil disturbance) of the surface soil layer of 0-10 cm and surface straw disturbance, the tine furrow openers with different structural parameters, including cutting edge thickness, cutting edge curve, penetration clearance angle and rake angle, were designed and tested under no-till conditions. Orthogonal test and single factor test were performed to analyze the effects of different parameters. Results showed that the rake angle, cutting edge thickness and cutting edge curve had significant effects on cross-sectional area of furrow (Af ) and disturbance of surface straw; the rake angle had a significant effect on soil bulk density. Soil types and operating depth had significant effects on soil disturbance caused by tine furrow openers. The concave type tine furrow opener produced the lowest soil disturbance and soil bulk density of seed furrow, the highest surface straw disturbance and the greatest content of WSA (>0.5 mm). With increasing rake angles of tine furrow opener, the width of seedbed (Wsb) and the Af decreased first and then increased, respectively, while the width of soil throw (Wst ) and the height of ridge (Hr) increased. The Wsb and Af created by tine furrow opener with 60° rake angle were significantly lower than that with others, respectively. The tine furrow opener with rake angle ranged from 45° to 60° created the lowest soil bulk density. As the penetration clearance angle increased, the content of WSA (>0.5 mm) decreased, but the effect of penetration clearance angle on the content of WSA was not significant. The cutting edge thickness had no significant effects on soil properties of seedbed. This study could provide a reference for optimal design of the tine furrow opener to create more suitable seedbed environment, and promote the application of the light no-till planters.Keywords: tine furrow opener, key parameter, no-till planter, soil disturbance, straw cover, bulk density, soil water-stable aggregatesDOI: 10.3965/j.ijabe.20160903.2259Citation: Zhang X C, Li H W, Du R C, Ma S C, He J, Wang Q J, et al. Effects of key design parameters of tine furrow opener on soil seedbed properties. Int J Agric & Biol Eng, 2016; 9(3): 67－80.